Posterior Reversible Encephalopathy Syndrome Due to Acute Water Intoxication in a Patient with Schizophrenia - Takaoka Y (International Medical Case Reports Journal, 2020)
Yohei Takaoka,1,2 Rie Akaho,1 Ken Inada,1 Hiroyuki Muraoka,1 Choryo Hokama,1 Atsuko Inoue,1 Katsuji Nishimura1 1Department of Psychiatry, Tokyo Women’s Medical University, Tokyo, Japan; 2Department of Psychiatry, Kuki Suzunoki Hospital, Kuki, Saitama, JapanCorrespondence: Rie AkahoDepartment of Psychiatry, Tokyo Women’s Medical University, Tokyo, JapanEmail akaho.rie@twmu.ac.jpAbstract: Posterior reversible encephalopathy syndrome (PRES) is a clinical syndrome that presents as transient cerebral edema (vasogenic edema), usually on a background of hypertensive encephalopathy, puerperal eclampsia, or immunosuppressant drug use. We describe a case of PRES that arose in the context of a psychiatric disorder. The patient was a 26-year-old woman with schizophrenia who was hospitalized upon falling into a catatonic stupor and then suffered acute anxiety leading to impulsive polydipsia and subsequent water intoxication. She lost consciousness, and brain magnetic resonance imaging revealed a high density area, primarily affecting the cortex and subcortical white matter in areas in the occipital and parietal lobes, leading to the diagnosis. We did not treat the hyponatremia by means of aggressive sodium supplementation but rather balanced the extracellular fluid by continuous infusion of isotonic electrolyte replacement fluid. The patient’s level of consciousness improved gradually, but a total 141 days passed before hospital discharge was appropriate. The prognosis for PRES is generally favorable, but irreversible neurological damage can occur. We believe, therefore, that brain magnetic resonance imaging should be performed promptly whenever PRES is suspected and that timely, appropriate treatment is of utmost importance. If PRES is observed in a psychiatric patient, it is important to investigate whether the condition might have been caused by water intoxication and to treat the condition accordingly.Keywords: posterior reversible encephalopathy, schizophrenia, water intoxication